Adaptability and stability patterns in endogamic hybrid maize families, obtained by the cryptic hybrids method - Lopes, Maria Teresa Gomes; Viana, José Marcelo Soriano; Lopes, Ricardo (Pesquisa Agropecuaria Brasileira, 2001)
The behavior of endogamic hybrid maize families was assessed using the cryptic hybrids method. This work was conduced by the maize breeding program at Departamento de Biologia of the Universidade Federal de Viçosa in Brazil. Twenty-two environments were used to characterize the hybrids using Eberhart & Russel and Carneiro methods. Using the first method, 15 hybrids were identified with yield higher than the general mean. Among them, 53.3% had general adaptability and high stability (84-6, 86-1, 86-19, 86-11, 86-15, 86-21, 86-27 and 86-10), and 20% had specific adaptation to favorable environments and high stability (86-22, 85-2 and 84-5). The hybrids 85-1, 85-3 and 86-2 had general adaptability associated with low stability, and also corresponding to a fraction 20% of the most productive hybrids. The last hybrid (86-8) corresponded to 6.7% and had specific adaptation to favorable environments and low stability. From the analysis using Carneiro's method, the hybrids 86-22, 86-8, 84-5, 85-2 and 86-19 were identified as the most adapted to favorable environments. The hybrids 86-11, 85-3, 86-27 and 86-2 were adaptable to unfavorable environments.